DEHUMANIZATION ISSUES DEPICTED IN MAIN CHARACTER IN MY SISTER KEEPER’S NOVEL: English - Hervandaru Satrio Wicaksono; Margawati, Prayudias (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study analyzes a story entitled My Sister's Keeper by Jodi Picoults through the lens of Haslam dehumanization. By focusing on the forms of dehumanization that occur and the consequences of these actions to the main character in the novel. By analyzing the main character of the story, I explored the forms of dehumanization that occur through Haslam's Mechanistic Dehumanization theory. Using the qualitative method helped me to identify the forms of dehumanization and its effects in the story. An example of a form of dehumanization that occurs today clearly and is still widely circulated is the workers with very minimum wages, but their work is very heavy and many make a mismatch between work and pay. This indicates that occupational slavery is still widely practiced, by not doing human beings properly but exploiting their labor with very low wages. In my findings, I show some evidence of the forms of dehumanization and designer baby that occur to the main character in his own family, what effects this has on her, and how the character finally acts with all the forms of dehumanization that occur to him without having a value. The purpose of my research is to examine and reveal that all forms of dehumanization are wrong and disregard a human life as it happens in the novel I am discussing. The analysis which I made will show the forms of dehumanization that occur and the consequences when these things happen to a person or human being who lives in this world, focusing on a dehumanization that occurs in the main character in the novel and what consequences this behavior has on a human being.